Post Evaluation of Ghowr Pozalich Small Hydropower by RET Screen Software - Mujeeb, Mujeebullah; Ahmadzai, Mujiburahman; Mirzazadah, Ainullah (Journal of Natural Sciences – Kabul University, 2022)
Small hydropower (SHP) has emerged as a renewable, easily developed, cost-effective, and environmentally friendly energy source. These characteristics have increased the value and prevalence of small hydropower development, leading to a new trend in renewable energy generation. Feasibility studies are essential for decision-making, estimating energy generation, project costs, and budget allocations for SHP schemes. RET Screen, a software commonly used in North America, is capable of evaluating energy generation, investment, and maintenance costs for small hydropower projects. This research applies RET Screen software to the Afghanistan context, evaluating the Ghowr Pozalich SHP, whose feasibility study was conducted in 2007. The results obtained from RET Screen are compared with the original feasibility study report.